A Case-Control Study Indicates that no Association Exists Between Polymorphisms of IL-33 and IL-1RL1 and Preeclampsia - Xiaoyan Ren; Mingzhen Guo; Caili Liu; Tao Huang; Qiang Li; Mengmeng Han; Weiqing Song; Xiuming Tang; Shiguo Liu (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Preeclampsia (PE) is a systemic inflammatory response syndrome involving varieties of cytokines, and previous studies have shown that IL-33 and its receptor IL-1RL1 play pivotal roles in the development of it. As a polygenetic hereditary disease, it is necessary to study the gene analysis for PE. Therefore, the present study was to determine whether IL-33 rs3939286 and IL-1RL1 rs13015714 associated with susceptibility to PE in Chinese Han women. Methods: 1,031 PE patients and 1,298 controls were enrolled and the genotyping for rs3939286 in IL-33 and rs13015714 in IL-1RL1 was performed by TaqMan allelic discrimination real-time PCR. Hardy-Weinberg equilibrium (HWE) was examined to ensure the group representativeness and Pearson's chi-square test was used to compare the differences in genetic distributions between the two groups. Results: No significant differences in genotypic and allelic frequencies of the two polymorphisms loci were observed between cases and controls. There were also no significant differences in genetic distributions between mild/severe and early/late-onset PE and control groups. Conclusion: Although our data suggested that the polymorphisms of IL-33 rs3939286 and IL-1RL1 rs13015714 might not be critical risk factors for PE in Chinese Han women, the results need to be validated in different nations.